2021
DOI: 10.1080/13880209.2020.1865409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antioxidant activities of nonfumigated and sulphur-fumigated Chrysanthemum morifolium cv. Hang-ju induced by oxidative stress

Abstract: Context:The traditional drying method, sun drying, for Chrysanthemum morifolium Ramat. cv. Hang-ju (Compositae) (HJ) is widely replaced by sulphur fumigation (SF), which has an unknown effect on its efficacy. Objective: To investigate protective effects of nonfumigated HJ (NHJ) and sulphur-fumigated HJ (SHJ) water extracts against oxidative stress and lipid peroxidation. Materials and methods: Sprague-Dawley rats were administered high-fat diet to induce hyperlipidaemia and randomly divided into eight groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The underlying mechanism is to activate adenosine monophosphate-activated protein kinase (AMPK) signaling pathway, suppress lipid synthesis gene expression and adipogenesis-related enzyme activity in white adipose tissue and liver, as well as increase gene expression involved in fatty acid oxidation [50]. Another study indicated that Hangju extract (1, 2 or 4 g crude drugs/kg/d) administration for 8 weeks can reduce the levels of TC, TG, LDL-C and LDL/HDL in serum of hyperlipidemia rats, increase serum HDL-C level, and alleviate oxidative damage induced by oxidized LDL (ox-LDL) in vitro [51]. Chrysanthemum has pleasing appearance and phytopharmacological activities attributed to its various flavonoids, such as luteolin, apigenin, acacetin, diosmetin and their glycoside derivatives [47,52].…”
Section: Chrysanthemi Flos (Juhua)mentioning
confidence: 99%
“…The underlying mechanism is to activate adenosine monophosphate-activated protein kinase (AMPK) signaling pathway, suppress lipid synthesis gene expression and adipogenesis-related enzyme activity in white adipose tissue and liver, as well as increase gene expression involved in fatty acid oxidation [50]. Another study indicated that Hangju extract (1, 2 or 4 g crude drugs/kg/d) administration for 8 weeks can reduce the levels of TC, TG, LDL-C and LDL/HDL in serum of hyperlipidemia rats, increase serum HDL-C level, and alleviate oxidative damage induced by oxidized LDL (ox-LDL) in vitro [51]. Chrysanthemum has pleasing appearance and phytopharmacological activities attributed to its various flavonoids, such as luteolin, apigenin, acacetin, diosmetin and their glycoside derivatives [47,52].…”
Section: Chrysanthemi Flos (Juhua)mentioning
confidence: 99%
“…The excessive superoxide reacts with NO to form peroxynitrite, consequently decreasing NO bioavailability and leading to endothelial dysfunction [36]. Previous studies have shown that CME attenuates oxidative damage in ECs [37,38], reduces oxidative stressinduced ECs adhesion [39], and has endothelium-dependent vasodilatory effects [40,41]. However, the mechanisms by which CME prevents endothelial dysfunction remain unclear.…”
Section: Introductionmentioning
confidence: 99%